Institutionalization of Minimum Service Standards (MSS) for Health Facilities in Nepal: Exemplary Plan-Do-Study-Act (PDSA) Cycle for Readiness and Service Availability - Thapa Pachya, Ambika; Pachya, Uttam; Amgain, Kapil; Upadhyaya, Madan Kumar (Journal of Karnali Academy of Health Sciences, 2023)
Access to health facilities alone, without quality services, does more harm than the benefit to the people’s health. Nepal has invested more than two decades in expansion of number of health facilities. Institutionalization of Minimum Service Standards (MSS) for health facilities in Nepal implemented by Ministry of Health and Population is an exemplary Plan-DoStudy-Act (PDSA) cycle for health facilities readiness and service availability for quality improvement. Thus, it is important to document the process for guiding institutionalization of tools. From its design, development, stakeholders’ engagement, implementation to development of action plan makes MSS lively and outcome-oriented tool. MSS for health facilities in Nepal is an effort of government to prepare foundation of readiness and service availability to move ahead with effective quality service utilization. Digitalization of the all sets of MSS, development of MSS to cover the existing type of the health facilities currently present in the country and access of data set for researchers is the way forward. Developing standards for national accreditation system and international collaboration is the next step to embrace. Furthermore, MSS gradually reported through selfassessment of the health facilities with occasional monitoring by the local, provincial and federal government and gap fulfillment through routine annual work plan and budgeting is the future direction. It is high time MoHP moves ahead with service specific quality improvement tools integrated with MSS assessment to prepare them for high quality health systems that can adapt to changing health needs and health shocks.